2013
DOI: 10.1002/tox.21873
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to benzidine caused apoptosis and malformation of telencephalon region in zebrafish

Abstract: Exposure to benzidine has been known to induce human cancers, particularly bladder carcinomas. In this study, the zebrafish model was used to investigate the developmental toxicity of benzidine. Embryos at 6 h postfertilization (hpf) that were exposed to benzidine exhibited embryonic death in a dose- and time-dependent manner. Benzidine induced malformations in zebrafish, such as small brain development, shorter axes, and a slight pericardial edema. High concentrations (50, 100, and 200 µM) of benzidine trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…These results show that diazinon is not a potent inducer of pmaip1. Contrary to our results, previous studies demonstrated that exposure to agricultural pesticides such as paraquat (a kind of herbicide) resulted in the elevation of apoptotic markers such as pmaip1 (20). As observed for MRC-5 cells exposed to diazinon, the cyp1a1 mRNA levels were induced by a mixture of 50 µM of diazinon and 20 or 80 µg/mL of the extract by 1.96 and 1.92 folds, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…These results show that diazinon is not a potent inducer of pmaip1. Contrary to our results, previous studies demonstrated that exposure to agricultural pesticides such as paraquat (a kind of herbicide) resulted in the elevation of apoptotic markers such as pmaip1 (20). As observed for MRC-5 cells exposed to diazinon, the cyp1a1 mRNA levels were induced by a mixture of 50 µM of diazinon and 20 or 80 µg/mL of the extract by 1.96 and 1.92 folds, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…In mammalians, Noxa protein plays an important role in apoptosis induced by mammalian reovirus [16,17]. In zebrafish, Noxa protein was a key mediator of apoptosis in both embryogenesis and adult [18,19]. When the embryos of zebrafish were injected with artificial noxa mRNA, cell apoptosis was observed and the apoptosis was dose-dependent [12].…”
Section: Introductionmentioning
confidence: 99%
“…These energy transfer efficiencies were particularly efficient for pyrene and benzo[ a ]pyrene, as well as for highly toxic aromatic amines such as 2-aminofluorene (23), 2-acetylaminofluorene (23), and benzidine (24), in combination with fluorophores 10 and 11 . Attempts to extend this cyclodextrin-promoted energy transfer to analytes 4–9 resulted in highly efficient energy transfer in several cases (Table 1), in particular for analytes 4 , 6 , and 8 in combination with fluorophore 10 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%